Incidencia de bacterias patógenas en carne de cerdo destinada al consumo humano en el Mercado Provisional del barrio San Bartolo - Intriago Molina, Yuli Elena (2023)
The objective of this research was to evaluate the incidence of pathogenic bacteria in pork intended for human consumption in the Provisional Market of San Bartolo neighborhood, Bolivar canton, Manabi province, through the identification of sources of contamination using a check list based on the INEN 2687:2013 standard for "Healthy Markets". Similarly, a microbiological analysis of samples was performed according to the requirements of the NTE INEN 1338 standard to identify the percentages of Escherichia coli and Staphylococcus aureus; so that, in the present investigation the sample was calculated with a confidence level of 90% (19 points of sale of meat) and meat samples were collected during the hours of 6:00 a.m. to 9:00 a.m., where it was determined that the microbiological requirements for raw meat were not met, as well as poor hygiene practices, handling and lack of control, which showed a deficit in the preservation of meat safety at the study site, where an average of 94,105.25 > 1.0 x 10^3 was obtained for Staphylococcus aureus and 14,194.74 > 1.0 x 10^2 for Escherichia coli with a positive asymmetric distribution. Therefore, the samples evaluated are not suitable for human consumption based on the requirements defined in INEN 1338.